KUALITAS DAGING ITIK FERMENTASI YANG DIRENDAM MENGGUNAKAN L. plantarum DENGAN LEVEL YANG BERBEDA DAN DISIMPAN PADA SUHU RENDAH - Hadju, Rahmawati (ZOOTEC, 2014)
THE CHEMICAL QUALITIES OF FERMENTED DUCK IMMERSED WITH DIFFERENT LEVELS OF L. plantarum AND STORED UNDER LOW TEMPERATURE. The objective of this research was study the effect of soaking time on chemical (pH, water content, acetic acid content and total lactic acid bacteria) of duck meat fermentation using L. plantarum. Ducks was done by soaking duck meat in culture L.plantarum and stroraged at cooling temperature. Soaking was done with different level of L. plantarum. This experiment was arranged in a completely randomized design consisted of five levels of L. plantarum. Data were analyzed by variance analysis. Significantly difference treatment effects on variable measures were tested using honestly significant difference (HSD). The result showed that treatments had significantly difference (P<0,01) on pH and total lactic acid bacteria of duck meat fermentation, but did not affect significant (P>0,05) on water content and acetic acid content of duck meat fermentation. Therefore, it can be concluded that soaking at 15% level of L. plantarum and storage at cooling temperature can conserve duck meat until 16 days and ducks fermentation were still constant. Keywords: Fermentation, duck meat, pH, water, acetic acid, lactic acid.